METHOD FOR IMPROVING THE EFFICIENCY OF INFORMATION EXCHANGE IN NETWORKS WITH NON-UNIFORM DATA FLOWS - Iskrenko, Yuriy; Kashkevych, Svitlana (Science-based technologies, 2026)
The article investigates the problem of improving the efficiency of information exchange in modern data transmission networks operating under conditions of uneven and dynamically changing traffic. The uneven nature of data flows, caused by differences in message generation intensity, fluctuations in channel load, and varying sensitivity of services to delays and packet losses, leads to degradation of quality of service indicators, congestion of individual network nodes, and inefficient use of channel bandwidth. Therefore, the development of adaptive traffic management methods capable of responding to changes in the network state in real time is an important scientific and practical task. The purpose of this study is to develop a method for improving the efficiency of information exchange in networks with non-uniform data flows based on adaptive bandwidth redistribution and dynamic adjustment of flow parameters. The proposed method is based on the analysis of traffic intensity, evaluation of the unevenness of data flows, and determination of their dynamic weights considering data priority, current delay, and packet loss probability. Based on these parameters, an adaptive mechanism for bandwidth allocation among data flows is formed, which allows minimizing network congestion and stabilizing quality of service indicators. To evaluate the effectiveness of the proposed approach, simulation modelling of a network with several data flows characterized by different traffic intensities was performed. The modelling results demonstrated that the proposed method provides a reduction in both average and peak packet delay, decreases packet losses, and improves the uniformity of channel bandwidth utilization compared to static resource allocation approaches. The obtained results confirm the effectiveness of the developed method and demonstrate the feasibility of its application in modern telecommunications and information systems to optimize data transmission processes in complex and dynamically changing network environments.